Continuous Flow and the Prothrombinase-Catalyzed Activation of Prothrombin - Schoen, Pieter; Lindhout, Theo; Willems, George; Coenraad Hemker, H (Thrombosis and Haemostasis, 1990)
The activation of prothrombin by prothrombinase was investigated in a continuous flow system at 25 °C. A glass capillary, containing a continuous phospholipid bilayer attached to the interior surface, was first perfused with factor Va. The factor Va bound to the phospholipid surface functioned as sites for the formation of prothrombinase, when subsequently a factor Xa and prothrombin containing solution was perfused. Under the conditions used, steady-state rates of prothrombin activation were attained after 4 to 15 min. The rates of prothrombinase formation increased with increasing factor Xa concentrations and flow rates, which is compatible with the assembly of prothrombinase being dependent on the flux of factor Xa to the phospholipid-bound factor Va. As long as factor Xa and prothrombin were present in the fluid phase the assembly of prothrombinase was apparently irreversible; during at least 20 min no loss of activity occurred. The steady-state rate of prothrombin activation was dependent on the surface concentration of prothrombinase, at 1.0 ΜM prothrombin and a shear rate of 82 s−1 the average rate was 870 mol thrombin/min per mol prothrombinase. In contrast to test tube experiments it was observed that in this flow system, the formation of Α-thrombin is favoured above the formation of meizothrombin (des fragment 1).